Pengaruh Influencer Marketing, Labelisasi Halal, dan Harga Terhadap Minat Beli Kosmetik Wardah (Studi Kasus Mahasiswi Universitas Islam Jember 2022) - ajeng, iylvina; Choiriyah, Farida Umi; Wijiono, Slamet (Lembaga Pusat Penelitian dan Pengabdian kepada Masyarakat (LP2M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
This study aims to determine: (1) the influence of influencer marketing on the intention to buy wardah cosmetics among Jember Islamic University students class of 2022, (2) the effect of halal labeling on the intention to buy wardah cosmetics among Jember Islamic University students class of 2022, (3) the effect of price on interest in buying wardah cosmetics for female students at the Islamic University of Jember class of 2022, (4) the influence of Influencer marketing, halal labeling and prices on the interest in buying wardah cosmetics for female students at the Islamic University of Jember class of 2022. The approach used is quantitative descriptive. The population in this study were all university students Islam Jember Class of 2022. The sampling technique used non-probability sampling with a total sample of 96 respondents. From the results of the analysis it can be seen that: The influencer marketing variable (X1) has an effect on buying interest (Y). Halal labeling variable (X2) has no effect on purchase intention (Y). The price variable (X3) has no effect on buying interest (Y). Meanwhile, simultaneously influencer marketing, halal labeling, and price have a positive and significant effect on purchase intention.